2020
DOI: 10.1519/jsc.0000000000003556
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Biochemical, and Neuromuscular Responses to Repeated Sprint Exercise in Eumenorrheic Female Handball Players: Effect of Menstrual Cycle Phases

Abstract: Graja, A, Kacem, M, Hammouda, O, Borji, R, Bouzid, MA, Souissi, N, and Rebai, H. Physical, biochemical, and neuromuscular responses to repeated sprint exercise in eumenorrheic female handball players: effect of menstrual cycle phases. J Strength Cond Res 36(8): 2268–2276, 2022—Very few studies have been interested in the relationship between ovarian hormones and physiological function in female athletes. The aim of this study was to assess the effect of menstrual phases (MP) on physical, neuromuscular, and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 42 publications
2
22
0
1
Order By: Relevance
“…Compared to anaerobic and aerobic performance, muscular strength seems more likely to be affected by MC phase. Muscular strength, determined by tests measuring maximal voluntary contractions and force production, was reported in five studies as being affected by MC phase [ 21 , 68 , 91 , 101 , 103 ], whilst five studies reported no MC phase effects on strength [ 52 , 71 , 94 , 95 , 99 ] and one study reported a change in some strength outcomes and no change in other strength outcomes [ 89 ].…”
Section: The Impact Of Menstrual Cycle Phase On Objectively Measurmentioning
confidence: 99%
See 4 more Smart Citations
“…Compared to anaerobic and aerobic performance, muscular strength seems more likely to be affected by MC phase. Muscular strength, determined by tests measuring maximal voluntary contractions and force production, was reported in five studies as being affected by MC phase [ 21 , 68 , 91 , 101 , 103 ], whilst five studies reported no MC phase effects on strength [ 52 , 71 , 94 , 95 , 99 ] and one study reported a change in some strength outcomes and no change in other strength outcomes [ 89 ].…”
Section: The Impact Of Menstrual Cycle Phase On Objectively Measurmentioning
confidence: 99%
“…However, multiple studies presented results that contradict this mechanism. Multiple studies found that there was no difference in strength between the late follicular and mid luteal phases [ 21 , 91 , 94 , 99 ], and strength outcomes were lower in the early follicular phase compared to the mid and late luteal phases [ 21 ], increased in the luteal phase [ 89 ], and significantly [ 103 ] and non-significantly [ 99 ] increased in the ovulatory phase.…”
Section: The Impact Of Menstrual Cycle Phase On Objectively Measurmentioning
confidence: 99%
See 3 more Smart Citations